2022
DOI: 10.29244/jekp.11.1.2022.1-18
|View full text |Cite
|
Sign up to set email alerts
|

Dampak Pembangunan Jalan Tol Trans Jawa terhadap Pertumbuhan Ekonomi di Jawa Tengah

Abstract: Infrastruktur jalan sebagai salah satu unsur dalam pelayanan jasa transportasi merupakan unsur penting dalam mendukung mobilitas di bidang ekonomi, sosial, dan budaya. Salah satu infrastruktur jalan yaitu jalan tol dibangun dengan tujuan meningkatkan efisiensi pelayanan jasa distribusi guna menunjang peningkatan pertumbuhan ekonomi untuk mewujudkan  pemerataan pembangunan serta keseimbangan dalam pengembangan wilayah. Penelitian ini menganalisis dampak keberadaan jalan tol Trans Jawa terhadap pertumbuhan ekono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
4
0
3
Order By: Relevance
“…Based on data from PUPR statistical information in 2019 [16] there are 20 toll road sections that began operating in the 2012-2018 period. 12 of them are in Central Java province, according to [17] the construction of toll roads in Central Java greatly affects the economy in the city/regency where the toll road is built. This has caused many agricultural lands to become victims of the toll road construction.…”
Section: Discussionmentioning
confidence: 99%
“…Based on data from PUPR statistical information in 2019 [16] there are 20 toll road sections that began operating in the 2012-2018 period. 12 of them are in Central Java province, according to [17] the construction of toll roads in Central Java greatly affects the economy in the city/regency where the toll road is built. This has caused many agricultural lands to become victims of the toll road construction.…”
Section: Discussionmentioning
confidence: 99%
“…The Trans-Java Toll Road in Indonesia, which extends from Port of Merak in Banten Province to Banyuwangi in East Java Province, is part of the National Strategic Project that connects major cities along the northern region of Java Island [1]. It has significantly contributed to enhancing economic growth, expanding employment opportunities, and accelerating socioeconomic progress [2]. According to the Indonesia Highway Regulatory Agency (BPJT), the total length of the operated toll road until June 2023 was 1.056,38 km.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that cities intersected by toll roads experience an enhanced economic growth rate, approximately 0.015 percent higher than cities devoid of such infrastructure. A shift in industrial locations towards toll gates, primarily to leverage their strategic placement, leads to increased regional revenue via taxation [1][2][3].…”
Section: Introductionmentioning
confidence: 99%